Advances in cardiac sounds monitoring enabled by triboelectric sensors - Xindan Hui; Hengyu Guo (Nano Trends)
Cardiac sounds sensor as a noninvasive instrument plays a pivotal role in the early diagnosis of various heart disease. In recent years, triboelectric nanogenerators (TENGs) have been employed widely for sensing different physiological information benefiting from abundant materials choices, simplicity of construction and low cost. More importantly, the fast saturated constitutive characteristic of the contact-separation mode (C-S) TENG demonstrates ultrahigh sensitivity in the detection of micromechanical quantities than traditional piezoelectric sensing mechanism. This article presents an overview of the C-S TENG enabled self-powered cardiac sounds monitoring, focusing on the working principle, performance comparison between C-S TENG and piezoelectric generator (PEG), and related applications. The challenges and future research directions of cardiac sounds sensor and C-S TENG toward micro-displacement region have also been proposed.